Self Concept Contribution to Bullying Behavior - Putri Eldes; Asmidir Ilyas (Jurnal Neo Konseling, 2019)
Individuals who imagine themselves successful tend to describe themselves with positive self-concepts, while individuals who imagine failing experiences more often describe themselves negatively. The contribution of self-concept is quite large in determining the behaviors of students in school because each student has a different concept of self. This study aims to empirically examine the contribution of self-concept to bullying behavior of students of SMK Negeri 10 Padang. This research is a descriptive correlational study with quantitative methods. Sampling in this study used purposive sampling technique with a total sample of 165 students. The research instrument used was a self-concept questionnaire and a bullying behavior questionnaire. The results of the study revealed that (1) the self-concept of students of SMK Negeri 10 Padang were mostly in a fairly good category (2) bullying behavior of students of Padang Vocational High School were mostly in the rare category (3) there was a significant contribution between self-concept of bullying students of SMK Negeri 10 Padang.